ARTIFICIAL INTELLIGENCE AND EDUCATION 5.0: EXPLORING THE LIMITS OF AI IN LOGICAL PROBLEMAS WITH EDUCATIONAL APPLICATION (Interdisciplinary Studies Journal, 2025)
This article explores the limits and potential of Artificial Intelligence (AI), specifically the ChatGPT-4.1 model, in solving logical-mathematical problems in educational contexts. Through a qualitative approach, simulations were conducted using various formulations of predefined problems. The analysis shows that AI performs well with clear questions but faces limitations when dealing with linguistic ambiguities and visual representations. The study highlights the role of the teacher as a critical mediator and emphasizes the importance of investigative practices for the responsible pedagogical use of AI, fostering the development of critical thinking and digital literacy, in alignment with the principles of Education 5.0.
Keywords: Artificial Intelligence; Education 5.0; Critical Thinking; Problem Solving; Digital Literacy